2010
DOI: 10.1038/leu.2010.205
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 and FBXW7 mutations have a favorable impact on early response to treatment, but not on outcome, in children with T-cell acute lymphoblastic leukemia (T-ALL) treated on EORTC trials 58881 and 58951

Abstract: Risk-adjusted treatment stratification in T-cell acute lymphoblastic leukemias (T-ALLs) is currently based only on early response to chemotherapy. We investigated the prognostic implication of hyperactivation of NOTCH pathway resulting from mutations of NOTCH1 or FBXW7 in children with T-ALL enrolled in EORTC-CLG trials. Overall, 80 out of 134 (60%) patients were NOTCH þ (NOTCH1 and/or FBXW7 mutated). Although clinical presentations were not significantly associated with NOTCH status, NOTCH þ patients showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
107
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 44 publications
11
107
1
5
Order By: Relevance
“…Despite major improvements in our understanding of the molecular genetics of T-ALL, [36][37][38][39] the mechanisms that lead to the abnormal proliferation and survival of T-lymphoblasts remain largely unknown. Therefore, treatment of this neoplasm remains a challenge for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Despite major improvements in our understanding of the molecular genetics of T-ALL, [36][37][38][39] the mechanisms that lead to the abnormal proliferation and survival of T-lymphoblasts remain largely unknown. Therefore, treatment of this neoplasm remains a challenge for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Development and progression of T-ALL have been linked to mis-regulation of Notch signaling (Aifantis et al, 2008;Clappier et al, 2010). In particular, we previously showed that Notch3 intracellular domain (N3 IC ) transgenic (tg) mice develop a very aggressive T-ALL with high penetrance, representing a suitable model of the human disease (Bellavia et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…35 advances in the molecular typing of leukemia, many new genetic alterations, including mutations and deletions, have been identified. However, their prognostic values have not been widely verified and the results may be controversial [24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%